Acceptance of ambulatory blood pressure monitoring in a semi-rural population in South Africa - Farisai Chiwanza; Yoland Irwin; Ros Dowse (AOSIS, 2020)
Background: Ambulatory blood pressure monitoring is a valuable tool that helps in providing an insight into the diagnosis and management of hypertension; however, no evidence exists of its acceptance in the diverse South African population. Aim: We assessed the acceptance of an ambulatory blood pressure monitor in patients attending public sector primary health care (PHC) clinics. Setting: Five PHC clinics in the Makana subdistrict in the Eastern Cape. Method: A cross-sectional study was conducted with 70 hypertensive patients. Eligible patients were between 40 and 75 years old, taking either enalapril and hydrochlorothiazide or enalapril, hydrochlorothiazide and amlodipine. Socio-demographic, clinical and acceptance data were collected. The monitor cuff remained in place for 24 h. Acceptance was assessed after the monitor was removed. An overall acceptance score was generated to classify acceptance as either good or poor. Results: The mean years of schooling was 5.9 years, with 22 reporting no school attendance. Generally, acceptance was good, with 70% of the population rating the technique as 'acceptable' (acceptance score of 23/30). Most participants reported minimal discomfort with only 13.3% reporting that it hindered normal daily activities. Night readings interrupted sleep in 43%, with extreme sleep disturbance (≥ 3 awakenings) reported in just over half the patients. Increased years of schooling was the only variable associated with acceptance score (r = −0.243, p = 0.042). Conclusion: Ambulatory blood pressure monitoring was generally well-accepted, with few adverse effects being reported. Use of this technique at PHC facilities could reduce the incidence of misdiagnosis and uncontrolled hypertension.